Overexpression of Nictaba-Like Lectin Genes from Glycine max Confers Tolerance toward Pseudomonas syringae Infection, Aphid Infestation and Salt Stress in Transgenic Arabidopsis Plants - Van Holle, Sofie; Smagghe, Guy; Van Damme, Els J. M. (Frontiers in Plant Science, 2016)
Plants have evolved a sophisticated immune system that allows them to recognize invading pathogens by specialized receptors. Carbohydrate-binding proteins or lectins are part of this immune system and especially the lectins that reside in the nucleocytoplasmic compartment are known to be implicated in biotic and abiotic stress responses. The class of Nictaba-like lectins (NLL) groups all proteins with homology to the tobacco (Nicotiana tabacum) lectin, known as a stress-inducible lectin. Here we focus on two Nictaba homologs from soybean (Glycine max), referred to as GmNLL1 and GmNLL2. Confocal laser scanning microscopy of fusion constructs with the green fluorescent protein either transiently expressed in Nicotiana benthamiana leaves or stably transformed in tobacco BY-2 suspension cells revealed a nucleocytoplasmic localization for the GmNLLs under study. RT-qPCR analysis of the transcript levels for the Nictaba-like lectins in soybean demonstrated that the genes are expressed in several tissues throughout the development of the plant. Furthermore, it was shown that salt treatment, Phytophthora sojae infection and Aphis glycines infestation trigger the expression of particular NLL genes. Stress experiments with Arabidopsis lines overexpressing the NLLs from soybean yielded an enhanced tolerance of the plant towards bacterial infection (Pseudomonas syringae), insect infestation (Myzus persicae) and salinity. Our data showed a better performance of the transgenic lines compared to wild type plants, indicating that the NLLs from soybean are implicated in the stress response. These data can help to further elucidate the physiological importance of the Nictaba-like lectins from soybean, which can ultimately lead to the design of crop plants with a better tolerance to changing environmental conditions.